The double-helix dipole - a novel approach to accelerator magnet design - Goodzeit, C.L.; Ball, M.J.; Meinke, R.B. (IEEE transactions on applied superconductivity, 2003)
We describe a new technology for superconducting dipoles that has significant advantages for use in particle accelerators. The dipole field is obtained by using concentric pairs of helically-wound coils that are tilted at opposite angles; this effectively cancels the solenoid component of the field and adds the dipole content of each layer. This coil configuration produces a dipole field with systematic errors <10/sup -8/ of the main field in 85% of the coil aperture. We show, using a design example, how many of the inherent problems with the traditional cosine theta type of coil are eliminated and the cost of development and manufacturing the magnets is substantially reduced.